1994
DOI: 10.1111/j.1365-2672.1994.tb03074.x
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐strain relationships among wine leuconostocs and their divergence from other Leuconostoc species, as revealed by low frequency restriction fragment analysis of genomic DNA

Abstract: Thirty Leuconostoc oenos strains, representing 28 different isolates, were distributed into 20 genomic groups according to PFGE patterns of restriction digests. The 8 bp-specific enzymes Sfi I, Not I and Asc I cleaved the Leuc. oenos DNA in a mean of 17, 11 and four fragments respectively and Sma I produced more than 50 fragments per genome. The strain differentiating capacity of the four enzymes was similar; only two related genomic groups failed to be distinguished by Asc I or Not I. Genomic relationships be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 27 publications
(24 reference statements)
3
36
0
Order By: Relevance
“…The CHEF system was used with 1 ' / o (w/v) agarose gels (Seakem GTG, FMC) and 0 5 x TBE (45 mM Tris, 45 mM boric acid, 1 mM EDTA, pH 8.0). Three run-types were applied for resolution of fragments in different ranges ( < 150 kb, 150-750 kb, >750 kb), as previously described (Tenreiro et al, 1994). The TAFE system was used with 1 '/O (w/v) agarose gels (Seakem LE, FMC) and 1 x TAE (40 mM Tris, 20 mM acetic acid, 1 mM EDTA, pH 8.0).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The CHEF system was used with 1 ' / o (w/v) agarose gels (Seakem GTG, FMC) and 0 5 x TBE (45 mM Tris, 45 mM boric acid, 1 mM EDTA, pH 8.0). Three run-types were applied for resolution of fragments in different ranges ( < 150 kb, 150-750 kb, >750 kb), as previously described (Tenreiro et al, 1994). The TAFE system was used with 1 '/O (w/v) agarose gels (Seakem LE, FMC) and 1 x TAE (40 mM Tris, 20 mM acetic acid, 1 mM EDTA, pH 8.0).…”
Section: Methodsmentioning
confidence: 99%
“…A macrorestriction analysis previously performed on 30 strains of 0. oeni (Tenreiro et al, 1994) showed that A d , NotI and SP, generating an average number of fragments between 4 and 17, were suitable enzymes for physical mapping. In strain PSU-1 these enzymes cleaved the chromosome into 4,12 and 16 restriction fragments, respectively (the 12th NotI fragment, of 6 kb, had not been previously detected).…”
Section: Restriction Digestion Patterns Of Genomic Dnamentioning
confidence: 99%
See 3 more Smart Citations